HIPOTESIS PENINGKATAN PENDAPATAN PETANI: PERSPEKTIF ISLAM - Riyardi, Agung (Universitas Muhammdaiyah Surakarta, 2002)
Optimizing the land can increase the small farmer income. That is, as the classical economic scale of farming state: